About the question of the legal entities responsibility for committing a genocide - Amanzholov, Zh.M.; Adibayeva, А.К.; Ryssaldiyeva, А.Ye. (KU Publ., 2022)
This article examines the issue of establishing binary liability for genocide both within the scope of the 1948 UN Convention and the criminal legislation of the countries that signed it. In this regard, the authors emphasize that the presence of a corpus delicti and criminal responsibility for legal organizations is based in part on a subject that is one of its components as well as individuals. To ascertain the issue’s relevance, a provision was also drafted stating that it must be resolved and referencing the 1985 UN Guidelines on developing a system for crime prevention and criminal justice of a new international economic order and existing international treaties of a universal and regional nature. In conclusion, the authors emphasize that filling the noted gap serves as a counteraction to the preconditions for genocide commission and, therefore, it should be a part of the Convention’s duties to its members.
Заңды тұлғалардың геноцид қылмысын жасағандығы үшін жауапкершілігі мәселесі туралы
К вопросу об ответственности юридических лиц за совершение преступления геноцида
Keywords: convention; genocide; responsibility; legal entities; obligations; individuals; international treaties; states-parties; national legislation; criminal justice